Efektivitas Aplikasi E-Samsat Sumut Dalam Pembayaran Pajak Kendaraan Bermotor di UPTD Pependa Medan Utara - Yesaya Putra Anugerah Manullang; Beltahmamero Simamora (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2026)
The e-Samsat Sumut application is a digital-based public service innovation that aims to make it easier for the public to pay motor vehicle taxes online. This study aims to assess the effectiveness of the E-Samsat Sumut application in motor vehicle tax payments at the UPTD Pependa Medan Utara. This study is a qualitative study with a descriptive approach. The data collection techniques used include interviews, observation, and documentation. The results of the study indicate that the e-Samsat Sumut application for motor vehicle tax payments has not been running effectively. This is indicated by the fact that the program's success indicators have not been met because there are still many technical obstacles, such as frequent system errors. The target success indicators have not been achieved because not all people are using this service. The program satisfaction indicators are still low due to frequent system disruptions. The input and output indicators show an imbalance between resources and results, and the overall objectives have not been optimally achieved because several obstacles have not been overcome. The overall objective indicators of the application have not been able to provide complete convenience and trust to the public in paying taxes online. The factors hindering the effectiveness of this application are frequent login failures and unreadable vehicle data, lack of socialization to the public, and low digital literacy.